Validation of the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group Neurotoxicity Questionnaire for the Latin American Population - Ivana Leao Ribeiro; Luz Alejandra Lorca; Rodrigo Cuevas-Cid; Snehil Dixit; Nicolás Yáñez-Benavides; Francisco Ortega-Gonzalez (International Journal of Breast Cancer)
Background. Chemotherapy-induced peripheral neuropathy is a common adverse effect of chemotherapeutic treatment and is associated with decreased quality of life. The aim of this study was to evaluate the validity and reliability of the neurotoxicity subscale of the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx) for the Chilean population. Methods. A cross-sectional study in which 101 participants with haematologic, colorectal, breast, gastric, gynaecological, and other types of cancer completed the FACT/GOG-Ntx. Content validity (n=14 health professionals evaluated the subscale in four categories: test-retest reliability (n=20 patients), dimensionality, internal consistency, and concurrent validity and discriminant validity. In all analyses, p<0.05 was considered significant. Results. There was an agreement among the evaluators for all categories of the subscale (Kendall’s coefficient, W=0.4, p<0.01) and moderate to high intrarater reliability (intraclass correlation coefficient=0.7–0.9). Of the 11 original items that make up the subscale, none was eliminated. The factor analysis generated four factors that represented 72.2% of the total variance. Cronbach’s α was 0.8 for the 11 items. Women showed greater compromise in emotional well-being and neurotoxicity symptoms compared with men, and age was directly correlated with the questions ‘I have difficulty hearing’ (r=0.2, p=0.019) and ‘I feel a noise or buzzing in my ears’ (r=0.2, p=0.03). Conclusion. The Chilean version of the FACT/GOG-Ntx neurotoxicity subscale is a valid and reliable scale for evaluating neurotoxicity symptoms in adult cancer survivors in Latin America. The scales also adequately distinguish between sex-based well-being among the afflicted population.